Oxygen isotope thermometry using quartz inclusions in garnet. (19th December 2016) - Quinn, R. J.; Kitajima, K.; Nakashima, D.; Spicuzza, M. J.; Valley, J. W.
Abstract: Oxygen isotope ratios of quartz inclusions (QI) within garnet from granulite and amphibolite facies gneisses in the Adirondack Mountains, NY were analysed and used to determine metamorphic temperatures. Primary QI for eight of 12 samples have δ 18 O values significantly lower than matrix quartz (MQ). The primary QI retain δ 18 O values representative of thermal conditions during garnet crystallization, whereas the δ 18 O values of MQ were raised by diffusive exchange with other matrix minerals (e.g. mica and feldspar) during cooling. The δ 18 O differences between QI and MQ show that garnet (a mineral with slow diffusion of oxygen) can armour QI from isotopic exchange with surrounding matrix, even during slow cooling. These differences between δ 18 O in MQ and QI can further be used to test cooling rates by Fast Grain Boundary diffusion modelling. Criteria for identifying QI that preserve primary compositions and are suitable for thermometry were developed based on comparative tests. Relations between δ 18 O and inclusion size, distance of inclusion to host–garnet rim, core–rim zonation of individual inclusions, and presence or absence of petrological features (healed cracks in QI, inclusions in contact with garnet cracks lined by secondary minerals, and secondary minerals along the inclusion grain boundary) were investigated. In this study, 61% of QI preserve primary δ 18 O and 39% were associated with features that were linked to reset δ 18 O values. If δ 18 O in garnet is homogeneous and inclusions are removed, laser‐fluorination δ 18 O values of bulk garnet are more precise, more accurate, and best for thermometry. Intragrain δ 18 O(Grt) profiles measured in situ by ion microprobe show no δ 18 O zonation. Almandine–rich garnet (Alm60–75 ) from each sample was measured by laser‐fluorination mass‐spectrometry (LF‐MS) for δ 18 O and compared with ion microprobe measurements of δ 18 O in QI for thermometry. The Δ 18 O(Qz–Grt) values for Adirondack samples range from 2.66 to 3.24‰, corresponding to temperatures of 640–740 °C (A[Qz–Alm] = 2.71). Out of 12 samples that were used for thermometry, nine are consistent with previous estimates of peak temperature (625–800 °C) based on petrological and carbon–isotope thermometry for regional granulite and upper amphibolite facies metamorphism. The three samples that disagree with independent thermometry for peak metamorphism are from the anorthosite–mangerite–charnockite–granite suite in the central Adirondacks and yield temperatures of 640–665 °C, ~100 °C lower than previous estimates. These low temperatures could be interpreted as thermal conditions during late (post‐peak) crystallization of garnet on the retrograde path.